Acrolein, an endogenous aldehyde induces Alzheimer's disease-like pathologies in mice: A new sporadic AD animal model. (January 2022) - Chen, Chen; Lu, Junfeng; Peng, Weijia; Mak, Marvin SH; Yang, Yang; Zhu, Zeyu; Wang, Shuyi; Hou, Jiawei; Zhou, Xin; Xin, Wenjun; Hu, Yafang; Tsim, Karl Wah Keung; et al.
Abstract: Alzheimer's disease (AD) is a common neurodegenerative disease that mainly affects elderly people. However, the translational research of AD is frustrating, suggesting that the development of new AD animal models is crucial. By gavage administration of acrolein, we constructed a simple sporadic AD animal model which showed classic pathologies of AD in 1 month. The AD-like phenotypes and pathological changes were as followed. 1) olfactory dysfunctions, cognitive impairments and psychological symptoms in C57BL/6 mice; 2) increased levels of Aβ1–42 and Tau phosphorylation (S396/T231) in cortex and hippocampus; 3) astrocytes and microglia proliferation; 4) reduced levels of postsynaptic density 95(PSD95) and Synapsin1, as well as the density of dendritic spines in the CA1 and DG neurons of the hippocampus; 5) high-frequency stimulation failed to induce the long-term potentiation (LTP) in the hippocampus after exposure to acrolein for 4 weeks; 6) decreased blood oxygen level-dependent (BOLD) signal in the olfactory bulb and induced high T2 signals in the hippocampus, which matched to the clinical observation in the brain of AD patients, and 7) activated RhoA/ROCK2/ p -cofilin-associated pathway in hippocampus of acrolein-treated mice, which may be the causes of synaptic damage and neuroinflammation in acrolein mice model. Taken together, the acrolein-induced sporadic AD mouse model closely reflects the pathological features of AD, which will be useful for the research on the mechanism of AD onset and the development of anti-AD drugs. Graphical Abstract: ga1 Highlights: Acrolein induced cognition impairment and affection dysfunction in mice. Acrolein induced olfactory disorders and Tau aggregation in the olfactory bulb. Acrolein increased the levels of Aβ and phosphorylated Tau in the cortex and hippocampus. Acrolein induced synaptic dysfunction in vitro and in vivo. Acrolein induced the activation of RhoA/ROCK2/ p -cofilin-associated pathway in hippocampus.